SPBM MELALUI MODEL INKUIRI DALAM MATERI LINGKUNGAN SEHAT DAN TIDAK SEHAT UNTUK MENINGKATKAN HASIL BELAJAR SISWA KELAS 3 SEMESTER 1 SDN KARANGSAMBIGALIH I - Sumiati Sumiati (MEDIA DIDAKTIKA, 2022)
This study aims to answer whether the application of SPBM through inquiry models in healthy and unhealthy environmental materials can improve student learning outcomes in semester 1 of SDN Karangsambigalih II SDN Karangsambigalih II, Sugio District, Lamongan Regency, Academic Year 2016/2017"?. Classroom action research was carried out in 2 cycles with each cycle of stages being planning, action, observation and reflection. The results showed that the application of SPBM through the inquiry model in healthy and unhealthy environmental material increased student learning outcomes. This can be seen from student learning outcomes in each cycle where in the pre-cycle there were 7 students or 43.75% who completed. then experienced an increase in cycle I, namely there were 10 students or 75% and in cycle II there were 12 students or 75%, an increase also occurred in the activeness of student learning, where in cycle I, namely there were 10 students or 62.5% and in cycle II there 14 students or 87.5%.